Wychowanie obywatelsko-patriotyczne na łamach czasopisma „Dziś i Jutro” w okresie międzywojennym - Jaworski, ks. Piotr; Juśko, Paweł (AUPC Studia ad Bibliothecarum Scientiam Pertinentia, 2023)
Dziś i Jutro (Today and Tomorrow) was a magazine for female youths that was published by the Ursuline Sisters. In 1919, the magazine was associated with the Union of Polish Ursulines; and in 1936, it was affiliated with the Roman Union of the Order of St. Ursula. The magazine was published until 1937, and its initiator was Sister Cecylia Łubieńska, later named superior general. The editors in chief were the following Ursuline Sisters: Julia Felicja Bronikowska (1925-1933), Zofia Zakrzewska (1933-1936), Jadwiga Szarska (1936-1937). The magazine was published in Kraków (1925-1936), and later in Poznań. It was a monthly publication; although from 1926-1927, an attempt was made to transform it into a biweekly. In total, thirteen volumes of this magazine were published. In this article, the content containing civic and patriotic values published in Dziś i Jutro was analyzed. Research has proven that this type of content was one of the main messages of the magazine. Civic and patriotic content was published more in the 1920s than in the 1930s. Additionally, lyrical and poetic texts, stories, novels in episodes, literary works, reports, speeches, and theatrical plays were also published. Their authors were university lecturers, writers, poets, artists, educators, and nuns, as well as students schooled by the Ursuline Sisters. The topics of the magazine contents varied, but the dominant topics were historical articles, biographies on distinguished Polish women, texts devoted to the heritage of Polish culture, folk traditions and customs, architectural monuments, nature, and native geography, social activities of youth organizations, and issues of Polish emigration. In these subjects, the value of good works for the motherland was often emphasized. This idea gained even greater importance in connection with the evolution of the Polish educational system towards the doctrine of state education that was introduced by the political camp of Marshal Józef Piłsudski. In the 1930s, the magazine also published articles related to the cult of Marshal J. Piłsudski. The analysis of the source material also showed the presence of other topics with civic and patriotic overtones that were related to economics, economic education, as well as the religious and moral formation of young girls.